BETTER SAFE HAVENS DURING COVID-19: A COMPARISON BETWEEN ISLAMIC AND SELECTED FINANCIAL ASSETS - Hedi Ben Haddad; Nader Trabelsi (Journal of Islamic Monetary Economics and Finance, 2021)
This study examines the safe haven properties of six assets (the S&P Technology Index, S&P GSCI Commodity Index, bitcoin, the Dow Jones Islamic Equity Index, the Dow Jones Global Sukuk Index and US Treasury bonds) during contiguous infectious diseases, employing the equity index returns of three regional markets (S&P500, S&P Europe, and S&P Asia-Pacific) over the period 2010 - 2020 Q2. In the research, information-rich methodological tools such as the Markov switching approach and the DCC-GARCH model are used. Our results suggest that Sukuk and bonds act as safe havens for different types of investors during the ongoing COVID-19 crisis. This property is, however, is not confirmed for the S&P Technology Index, Commodity Index, bitcoin or the DJ Islamic Equity Index. Moreover, using the time-varying VAR model and the new measure of pandemic uncertainty proposed by Baker et al. (2020), the results demonstrate that the COVID-19 pandemic has led to uncertainty and heightened volatility spillovers among regional equities and the safe haven assets examined. The key results of the study are robust and useful for portfolio managers and investors.